THE ROLE OF LEADERSHIP TRAINING IN IMPROVING THE PROSOCIAL BEHAVIOR OF STUDENTS - Fathusy Syarif (As-Sulthan Journal of Education, 2026)
Prosocial behavior, which includes the act of helping others without expecting anything in return, is very important in building the character of students in Islamic boarding schools. This article discusses how leadership training programs can help students develop prosocial behavior. Through a qualitative approach, this study shows that leadership training not only increases students' awareness of the importance of helping others, but also provides the necessary skills to contribute positively in society. The results of the study show that students who participate in this program are more active in social activities and have a better understanding of leadership values. In addition, this program encourages students to internalize the values of empathy, responsibility, cooperation, and effective communication. The training process also strengthens students' ability to solve problems collectively, make wise decisions, and motivate peers to behave positively. Thus, leadership training has proven to be an effective strategy to shape the social character of students and prepare them to become agents of change in the pesantren environment and the wider community.